An IoT application for Home Control focused on Assistive Technology - Peroba, Jamir Alves; Costa, Vinícius Kruger da; Rodrigues, Andréia Sias; Tavares, Tatiana Aires; Machado, Marcelo Bender; Xavier, Krishna Ferreira; Yamin, Adenauer; Cardoso, Rafael Cunha (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
This paper presents the development of IOM4Home, an IoT (Internet of Things) based application for home environment controlling, specially designed for people with motor disabilities. The main goal is to provide a software/hardware solution that relies on IOM (Interface Óculos Mouse) to control home environments. IOM consists in an Assistive Technology based device used to control a computer in a hands-free way. To achieve this objective, this paper details a proposal composed by two main elements: an assistive Interface designed especially for IOM; and an IoT system to manage and exchange data between the available home domotics and the developed interface. The paper also presents a test scenario, highlighting the main results obtained with the evaluation. Finally, the article presents its conclusions and the future developments of the project